Lectotypification of Rhynchosia acuminatifolia (Leguminosae) - Mishra, Ajay K.; Gupta, Vedhika; Wagh, Vjay V. (Phytotaxa, 2020)
During the revisionary study on the genus Rhynchosia in India, it was observed that no lectotype has been designated for Rhynchosia acuminatifolia Makino. Therefore, the original material of the species is here established and lectotype is selected.